2000
DOI: 10.1152/ajpheart.2000.279.4.h1869
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of action potential head-tail interaction during reentry in cardiac tissue: ionic mechanisms

Abstract: In a sufficiently short reentry pathway, the excitation wave front (head) propagates into tissue that is partially refractory (tail) from the previous action potential (AP). We incorporate a detailed mathematical model of the ventricular myocyte into a one-dimensional closed pathway to investigate the effects of head-tail interaction and ion accumulation on the dynamics of reentry. The results were the following: 1) a high degree of head-tail interaction produces oscillations in several AP properties; 2) Ca(2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…In an experimental study, Frame and Simson [406] found that the reentry could be unstable with fluctuating circulating time and APD, exhibiting a quasi-periodic pattern (Fig.45b). This behavior can be readily recapitulated in computer simulations using a 1D ring [241, 345, 407411], as shown in Fig.45c for comparison with the experimental data. The quasi-periodic behavior has been well-studied theoretically, first by Courtemanche et al [345, 408] who developed an integral-delay equation for a wave circulating in a ring, i.e., dfalse(xfalse)=xLxdsθfalse(sfalse)dsafalse(xLfalse) where d ( x ) is the DI at location x, a ( x ) is the APD at location x which is determined by the APD restitution function a ( x )= f [ d ( x )], θ( x ) is the CV at location x which is determined by the CV restitution function θ( x )= g [ d ( x )], and L is the perimeter of the ring.…”
Section: Electrical Wave Dynamics In Tissue and Organmentioning
confidence: 86%
“…In an experimental study, Frame and Simson [406] found that the reentry could be unstable with fluctuating circulating time and APD, exhibiting a quasi-periodic pattern (Fig.45b). This behavior can be readily recapitulated in computer simulations using a 1D ring [241, 345, 407411], as shown in Fig.45c for comparison with the experimental data. The quasi-periodic behavior has been well-studied theoretically, first by Courtemanche et al [345, 408] who developed an integral-delay equation for a wave circulating in a ring, i.e., dfalse(xfalse)=xLxdsθfalse(sfalse)dsafalse(xLfalse) where d ( x ) is the DI at location x, a ( x ) is the APD at location x which is determined by the APD restitution function a ( x )= f [ d ( x )], θ( x ) is the CV at location x which is determined by the CV restitution function θ( x )= g [ d ( x )], and L is the perimeter of the ring.…”
Section: Electrical Wave Dynamics In Tissue and Organmentioning
confidence: 86%
“…Accurate repolarization rate (i.e. time between APD30 and 90) for the restitution protocol is crucial for simulating any phenomenon related to reentrant arrhythmia, where head-tail interactions determine refractoriness and vulnerability[83]. Use of new undiseased data for currents that are active during the plateau and phase-3 of the AP (I CaL , I NaCa , I Kr and I Ks ) contributed to the correct repolarization rate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the larger Ca-to-Vm gain in the canine compared with guinea pig is due to differences in ion channel expression levels and kinetic properties 21 . On the background of smaller I Kr and I Ks in the canine 22 , in conjunction with a much smaller I Ca during the late AP plateau 23 , Ca transient-induced changes in I NCX have a much greater modulatory effect on AP repolarization, identifying I NCX as the predominant Ca-to-Vm coupler during alternans. The other Ca-dependent currents, I Ca and I to , play a role in shaping the AP during its initial plateau phase, causing crossover between consecutive APs during alternans, but have a minimal effect on APD.…”
Section: Discussionmentioning
confidence: 99%